A Participatory Curricula for Community Health Workers and Supervisors to Increase HIV Health Outcomes - Rajabiun, Serena; Baughman, Allyson; Sullivan, Marena; Poteet, Beth; Downes, Alicia; Davich, Jo Ann Whitlock; Phillips, Simone; Jackson, Precious; Miles, LaTrischa; Drainoni, Mari-Lynn; Evans, Emmitt Maurice; Bachman, Sara S.; et al. (Frontiers in Public Health, 2021)
Community Health Workers (CHWs) are becoming essential members of the HIV workforce as emerging evidence demonstrates their effectiveness in engaging people with HIV into care and treatment. In 2018, among the estimated 37,000 persons who received an HIV diagnosis, the majority were from racial ethnic minority communities. CHWs serve as a bridge between the community and health care system and have the potential to address structural inequities and reduce the stigma, discrimination and other barriers that prevent people living with HIV from seeking and staying in care and treatment. Effective CHW integration into the HIV primary care team requires a training and supervision system that is culturally responsive to the complex social and medical needs of people with HIV. This article describes a comprehensive training approach and curricula for CHWs and supervisors and its impact on the health care team. Grounded in a Popular Education model and using the CHW core consensus competency (C3) framework, a team of experts in HIV, training and supervision, including CHWs working in HIV care and treatment developed an 80-hour CHW and 20-hour supervisor curricula. The trainings were delivered via in-person and virtual sessions over the course of two years. Using a mixed method evaluation, 23 CHWs and 22 supervisors across 10 clinic sites in eight states participated in the training sessions. Measures included knowledge and confidence related to HIV specific content, supporting clients with managing stigma and discrimination, ability to communicate with other team members and helping clients navigate the services system. CHWs reported improved skills with documentation in the electronic health record, helping clients with treatment adherence challenges and educating on lab results. Supervisors reported learning strategies for assigning clients to CHWs, self-care techniques, providing strengths-based feedback, and mentoring and coaching. The participatory practice-based curricula allowed supervisors and CHWs to share experiences and solicit input from peers for problem resolution and implementation of new policies and practices. This training approach focused on HIV specific content with core competency training could serve as a model for CHWs working in primary care settings and with populations experiencing multiple chronic health conditions and social needs.